Identifying the Factors of Sustainable Competitive Advantage to Maintain the Continuity and Performance of MSMEs In the Pandemic Era - Wawan DHEWANTO; Anindia P. PUTRI; Gita HINDRAWATI (Communications of International Proceedings, 2022)
Covid-19 provides new pandemic conditions and has a significant impact, especially on MSMEs performance. The severe impact of the pandemic on MSMEs has hampered business continuity and faltering economic growth due to the critical role of MSMEs in the country's economy, especially in developing countries. From this new pandemic situation, it is necessary to develop a comprehensive business continuity plan and have a sustainable competitive advantage so that businesses can survive in the high competition among MSMEs in the pandemic era. Previous research has not identified what factors an entrepreneur must have to build a business that has a sustainable competitive advantage. Therefore, to fill this gap, this study tries to analyze what factors are needed to create a sustainable competitive advantage that will ensure the continuity and performance of MSMEs. This research was conducted in Indonesia, one of the developing countries with the highest Covid-19 cases in Southeast Asia. Data will be collected through a questionnaire which will be processed using SEM-PLS. This study offers managerial implications for entrepreneurs to identify the factors that support a sustainable competitive advantage to maintain the performance and continuity of MSMEs.
Keywords: Sustainable Competitive Advantage; Business Continuity; SMEs’ Performance; COVID-19.